Организация самостоятельной работы учащихся на уроке в условиях малокомплектной сельской школы - Токтасынова, Г.Н. (My University, 2016)
The article is devoted to the peculiarities of the educational process in an ungraded rural schools with combined classes. The article deals with one of the leading and activating forms of education – individual work. It is considered the role of the teacher in the organization and support of individual student’s work, what kind of forms and methods promote increase of the learning effect of individual work and all of the learning process of students in ungraded rural schools.
Keywords: ungraded rural school; combined classes; individual work